A comparison between Lynch syndrome and sporadic colorectal cancer survivors’ satisfaction with their healthcare providers - Burton‐Chase, Allison M. (Cancer Med, 2017)
This study evaluated provider satisfaction in a sample of colorectal cancer (CRC) survivors with and without Lynch syndrome (LS). Participants were case–case‐matched CRC survivors with (n = 75) or without (n = 75) LS (mean age of 55; range: 27–93). Participants completed a mailed questionnaire assessing demographics, clinical characteristics, healthcare utilization, psychosocial variables, and provider satisfaction. LS CRC survivors reported lower provider satisfaction scores on three subscales of the Primary Care Assessment Survey: communication (78.14 vs. 83.96; P < 0.05), interpersonal treatment (78.58 vs. 85.30; P < 0.05), and knowledge of the patient (60.34 vs. 69.86; P < 0.01). Among LS CRC survivors, predictors for mean communication and trust subscale scores were location of treatment and socioeconomic status. Higher mean depression scores also were associated with trust, while social support predicted higher satisfaction with communication. Sporadic CRC survivor satisfaction is driven largely by age (communication, interpersonal treatment) and patient anxiety (communication), while seeing a provider more often was associated with increased satisfaction with knowledge of the patient. LS CRC survivors reported lower levels of provider satisfaction than sporadic CRC survivors. LS survivors who received care at The University of Texas MD Anderson Cancer Center, a comprehensive cancer center (CCC), reported higher satisfaction than those receiving care at other institutions. Depressive symptoms and socioeconomic status may impact provider satisfaction ratings. Exploration of other potential predictors of provider satisfaction should be examined in this population. Additionally, further research is needed to examine the potential impact of provider satisfaction on adherence to medical recommendations in LS CRC survivors, particularly those being treated outside of CCCs.